2006
DOI: 10.2320/matertrans.47.1769
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization Behavior and Texture Formation of Rapidly Annealed Cold-Rolled Extralow Carbon Steel Sheets

Abstract: The influence of a heating rate up to 1000 C/s on recrystallization behavior and texture formation of an extralow carbon steel sheet was investigated. To discuss the experimental results of this investigation, a mathematical model for predicting recrystallization behavior was developed. An analysis using the model shows that the heating rate influences the apparent thermal activation energy of recrystallization. At a higher heating rate, C dissolved from cementite and AlN precipitated during heating decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
5
16
0
Order By: Relevance
“…The pinning effect of carbon atoms on the dislocation structure is claimed to play a significant role in slowing the recrystallization and decreasing the ferrite recrystallized fraction at the same heating temperatures. Similar findings are reported by Stockemer and Vanden Brande [14] and Senuma et al [15]. It is also reported that the recrystallization is completed before the onset of austenite formation in low and very low carbon steels, as well as in interstitial free (IF) steel [16].…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The pinning effect of carbon atoms on the dislocation structure is claimed to play a significant role in slowing the recrystallization and decreasing the ferrite recrystallized fraction at the same heating temperatures. Similar findings are reported by Stockemer and Vanden Brande [14] and Senuma et al [15]. It is also reported that the recrystallization is completed before the onset of austenite formation in low and very low carbon steels, as well as in interstitial free (IF) steel [16].…”
Section: Introductionsupporting
confidence: 77%
“…It is also reported that the recrystallization is completed before the onset of austenite formation in low and very low carbon steels, as well as in interstitial free (IF) steel [16]. Results on the texture evolution during fast and ultrafast heating of ULC steel and low carbon steel heating have been published elsewhere [4][5][6][7]14,15,17,18]. The orientation measurements do not show significant deviations from {111}<uvw> ND fiber [19,20], suggesting that the recrystallization textures in ferrite are practically independent of the heating rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter b is the function of temperature, reduction in cold rolling and initial grain size, and n is a constant that varies from 1 to 4 depending on the growth behavior of the recrystallizing grains. Equation (3) Recent research on the prediction of the recrystallization behavior of cold-rolled extra-low-carbon steel sheets using a JMAK-type equation 6) is introduced in the following. Figure 3 shows the recrystallization behavior of steel samples coldrolled to 80% and subsequently heated with various heating rates.…”
Section: Prediction Models For Recovery and Recrystallizationmentioning
confidence: 99%
“…Influence of the heating rate on the recrystallization behavior of an extralow carbon steel sheets cold rolled to 80%. 7) Experimental data were compared with the result calculated. …”
mentioning
confidence: 99%